2014
DOI: 10.2147/ijn.s66318
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance-like innate immunity and spleen injury: a novel discovery via the weekly administrations and consecutive injections of PEGylated emulsions

Abstract: There has been an increasing interest in the study of the innate immune system in recent years. However, few studies have focused on whether innate immunity can acquire tolerance. Therefore, in this study, we investigated tolerance in the innate immune system via the consecutive weekly and daily injections of emulsions modified with polyethylene glycol (PEG), referred to as PEGylated emulsions (PE). The effects of these injections of PE on pharmacokinetics and biodistribution were studied in normal and macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Based on these known immunosuppressive effects of PEG, it is possible that PEG components of nanoparticles may contribute to carrier-induced suppression of antitumor immunity. This hypothesis is supported by a recent report that PEG-lipid nanoemulsions (mean particle size 125 nm) induced immunologic tolerance that was mediated by macrophages ( Wang et al, 2014 ). However, this study did not include a non-PEG lipid control, and it is unclear whether these immunosuppressive effects were due to PEG, lipid, or both components.…”
Section: Contribution Of Polyethylene Glycol To Immunomodulationsupporting
confidence: 61%
“…Based on these known immunosuppressive effects of PEG, it is possible that PEG components of nanoparticles may contribute to carrier-induced suppression of antitumor immunity. This hypothesis is supported by a recent report that PEG-lipid nanoemulsions (mean particle size 125 nm) induced immunologic tolerance that was mediated by macrophages ( Wang et al, 2014 ). However, this study did not include a non-PEG lipid control, and it is unclear whether these immunosuppressive effects were due to PEG, lipid, or both components.…”
Section: Contribution Of Polyethylene Glycol To Immunomodulationsupporting
confidence: 61%
“…Moreover, recent evidence in patients with ovarian cancer showed that circulating monocyte numbers and plasma CCL2 levels correlated with PLD clearance [37] and plasma PLD levels [63], respectively. In addition, CCL2 knockout mice bearing ovarian tumor xenografts were found to have altered clearance of PLD as compared to control mice [62,63]. These data further support a link between PLN uptake by myeloid cells of the monocyte-macrophage lineage and their immune functionality.…”
Section: Discussionmentioning
confidence: 81%
“…A lower index indicates faster elimination in blood and a more severe ABC phenomenon. To describe the extent of the ABC phenomenon more intuitively, we suggested a four-level division based on the ABC index within 30 min: 0–0.5 for a significant ABC phenomenon, 0.5–0.7 for a moderate ABC phenomenon, 0.7–0.9 for a weak ABC phenomenon, and 0.9–1.0 for no ABC phenomenon. , In this study, we calculated the ABC index with final times ranging from 15 to 720 min (data not shown). We determined that the ratio of AUCs was more comparable within 60 min than within 30 min, suggesting that AUC (0–60min) was a suitable parameter for assessing the magnitude of the ABC phenomenon.…”
Section: Resultsmentioning
confidence: 99%